Effect of Long-term Use of Steroidal Anti-inflammatory Drugs on the Periodontal State: A Review - Rinkee Mohanty1, Rashmita Nayak2, Gatha Mohanty3, Abhaya Das4, Utkalika Das5, Aishwarya Bal6 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Corticosteroids are chemically similar to endogenous cortisol and mostly prescribed for their antiinflammatoryand immunosuppressive properties, which are due to the inhibition of phospholipase A2activity. These drugs are extensively used in the treatment of a plethora of autoimmune disorders suchas rheumatoid arthritis, various breathing disorders and also disorders of connective tissue. In the fieldof dentistry these drugs are prescribed in most of the mucocutaneous disorders such as they are mostlyused in inflammatory diseases such as oral lichen planus, pemphigus, and oral stomatitis to alleviate postoperativediscomfort and swelling. These drugs can be administered systemically,topically or asinhalationaltherapy. Evidence concludes that short term corticosteroids possess antiresorptive properties and its localapplication shows a favourable effect on the periodontal ligament, but when administered systemically fora long period could lead to periodontal diseases as it has shown to increase attachment with alveolar boneand destruction of transseptalfibers. Oral manifestations are dependent on duration,dose and frequency ofuse. It is commonly associated withmoniliasis, dental caries,altered taste sensation, ulceration of the tongue,buccal mucosa, and gingiva due to xerostomia,gingival inflammation, periodontal inflammation,and immunesuppression. They can either cause dramatic improvement or dramatic adverse reactions which can lead toa considerable increase in the distributionof periodontal disorders. In patients on long-term corticosteroidtherapy, oral health is generally not given importance during management. Hence this review explains aboutvarious effects of different types of corticosteroids on periodontium used in dentistry.